Ruthenium indenylidene “1st generation” olefin metathesis catalysts containing triisopropyl phosphite - Guidone, Stefano; Nahra, Fady; Slawin, Alexandra M. Z.; Cazin, Catherine S. J. (Beilstein Journal of Organic Chemistry, 2015)
The reaction of triisopropyl phosphite with phosphine-based indenylidene pre-catalysts affords “1st generation” cis-complexes. These have been used in olefin metathesis reactions. The cis-Ru species exhibit noticeable differences with the trans-Ru parent complexes in terms of structure, thermal stability and reactivity. Experimental data underline the importance of synergistic effects between phosphites and L-type ligands.
Keywords: 1st generation; indenylidene; metathesis; phosphite; ruthenium